PENGARUH JUMLAH SALURAN MASUK UDARA TERHADAP DISTRIBUSI KECEPATAN UDARA PENGERING PADA ALAT PENGERING TIPE SWIRLING FLUIDIZED BED - Satya Andika Putra; Novrinaldi Novrinaldi Novrinaldi (Widyariset, 2020)
Numerical and experimental studies have been carried out on the effect of inlet air number to the air velocity distribution in the drying chamber of the Swirling Fluidized Bed Dryer (SFBD). The main components of SFBD are a drying chamber, plenum chamber, center body, distributor, inlet air, heater, and blower. Numerical analysis was performed using the finite volume method on a three-dimensional model using computational fluid dynamic (CFD) software. An experimental study was carried out by measuring the air velocity at eight measurement points in the drying chamber. The results showed that using two inlet air produced a more uniform distribution of air velocity compared to one inlet air.